2010
DOI: 10.1007/s11256-009-0136-z
|View full text |Cite
|
Sign up to set email alerts
|

Class, Identity, and Teacher Education

Abstract: This paper explores the possibilities of working with White, workingclass teacher education students to explore the ''complex social trajectory'' (Reay in Women's Stud Int Forum 20(2):225-233, 1997a, p. 19) of class border crossing as they progress through college. Through analysis of a course that I have developed, Education and the American Dream, I explore political and pedagogical issues in teaching the thousands of teacher education students who are the first in their families to attend college about soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Moreover, whilst novice teachers might explore issues around social class (alongside race and gender) in teacher education/training in both the UK and other structurally unequal Western countries, this is mostly under the guise of understanding learner identities where the focus rarely shifts towards how teachers' own identities are shaped by these factors (Allard and Santoro 2006;Santoro 2009). Arguably, both existing and novice teachers have little understanding of their own class identities that are often so deeply embedded they are rarely even visible, never mind questioned or problematised (Ladson-Billings 2001;Van Galen 2010). As such, they are likely to be 'unaware of the effects of their own classed identities on their professional practice' (Gazeley and Dunne 2007, 413) with little understanding of the ways in which the education system they have entered is inequitable on the grounds of class.…”
Section: Cultural Analyses Of Classmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, whilst novice teachers might explore issues around social class (alongside race and gender) in teacher education/training in both the UK and other structurally unequal Western countries, this is mostly under the guise of understanding learner identities where the focus rarely shifts towards how teachers' own identities are shaped by these factors (Allard and Santoro 2006;Santoro 2009). Arguably, both existing and novice teachers have little understanding of their own class identities that are often so deeply embedded they are rarely even visible, never mind questioned or problematised (Ladson-Billings 2001;Van Galen 2010). As such, they are likely to be 'unaware of the effects of their own classed identities on their professional practice' (Gazeley and Dunne 2007, 413) with little understanding of the ways in which the education system they have entered is inequitable on the grounds of class.…”
Section: Cultural Analyses Of Classmentioning
confidence: 99%
“…The evidence presented here offers further support for particular approaches developed in the US and Australia, that the specific discussion of the social and cultural backgrounds and identities of new teachers in an open but critical way should be on the agenda for all novice teachers as they learn to teach (Gay 2010;Santoro 2009). In this way, the types of tensions that arise as a result of social class boundary crossing in teaching could be foregrounded and discussed reflexively out in the open in a 'safe' space, especially when issues of social class are directly explored (Jones and Vagle 2013;Van Galen 2010). This would then offer assistance to novice teachers that may prevent them being constrained by their class or forced into accepting the only way to avoid these limitations, is to strategise, deny or disassociate with their class identities.…”
Section: Implications For Initial Teacher Education and Trainingmentioning
confidence: 99%
“…In the field of education, researchers have attempted to dismantle the middle‐class habitus by problematizing privilege among veteran and preservice teachers (Adair, ; Allard & Santoro ; Galen, ). In Galen's () study of working‐class teacher education students crossing class borders through college education, participants were encouraged to reflect on how their own educational experiences were inextricably tied to class so that they might “understand the many barriers that stand between marginalized students and adult success” (p. 255). The study resulted in students understanding how class boundaries are “constructed and maintained not only in occupational hierarchies but also in the dailiness of social life” (p. 257).…”
Section: Deconstructing Social Class In the Second Language Classroommentioning
confidence: 99%
“…These socially constructed labels, however, often fluctuate and have vague boundaries, making identity studies on class somewhat problematic, especially when institutions and those in power position individuals differently from how they identify—a particular tension between material and social conceptualizations of class. For example, Galen's () study in a university teacher education program found that students often positioned themselves as middle class due to their access to higher education, while the institution marked them as working class due to family income. The institution conceptualized social class around material indices of wealth, an economic measurement, while students considered the social and cultural capital (Bourdieu, ) of college education to be a marker of middle‐class status, a social perspective.…”
mentioning
confidence: 99%